Serum uric acid in new and recent onset primary hypertension - N N Anand; V Padma; Arun Prasad; Krishna Chaitanya Alam; M. S. A. Syed Mohammed Javid (Journal of Pharmacy and Bioallied Sciences, 2015)
Introduction: Hyperuricemia is common among adults with prehypertension, especially when the microalbuminuria is present. Hyperuricemia precedes the development of hypertension. Aim: (1) To find the association of hyperuricemia in new-onset hypertensive patients. (2) To find the association of hyperuricemia in hypertensive patients with regard to gender and risk factors such as smoking and central obesity. Material and Methods: A total of 50 adults aged between 20 and 50 years who had mild early hypertension were selected for the study. Fifty controls without hypertension were enrolled and investigated. Results: The association between uric acid (UA) and hypertension was analyzed using Student′s t-test and statistical difference were assessed using Pearson coefficient. The study showed a significant difference in UA between the hypertensive subjects and the normotensive controls. There was not a significant difference between waist abnormality, smoking and UA in cases. Males have a higher degree of hyperuricemia than females in hypertensive patients. Conclusion: Serum UA is strongly associated with blood pressure (BP) in new and recent onset primary hypertension. The remarkable association of UA with BP in adults is consistent with recent animal model data and the hypothesis that the UA might have a pathogenic role in the development of hypertension.